2010
DOI: 10.1093/humrep/deq116
|View full text |Cite
|
Sign up to set email alerts
|

Fall in implantation rates following ICSI with sperm with high DNA fragmentation

Abstract: These observations may help to resolve the issues about how, and to what extent, sperm DNA damage impacts upon the success of IVF and ICSI procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
87
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 39 publications
11
87
0
3
Order By: Relevance
“…Twenty studies [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] were indentified for our meta-analysis. The flow chart of the process for the identification of the studies were shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty studies [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] were indentified for our meta-analysis. The flow chart of the process for the identification of the studies were shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 15 studies with CP as the outcome measurement was included in the meta-analysis [7,8,10,12,[15][16][17][19][20][21][22][23][24][25][26]. These studies were divided into 3 groups according to the DFI cutoff value (>27 %, 15-27 %, ≤15 %) as described previously.…”
Section: Dfi and Cpmentioning
confidence: 99%
See 1 more Smart Citation
“…Fertilization with DNA-damaged sperm increases the risk of promoting pregnancy loss in mammals (Speyer et al 2010), arrest in embryo development or embryo death (Perez-Cerezales et al 2010b, Gawecka et al 2013, birth defects, chromosomal abnormalities and other genetic diseases (Fernandez-Gonzalez et al 2008, Barroso et al 2009, Schulte et al 2010, Marchetti et al 2015. The DNA-repairing activity relies on the oocyte machinery once the fertilization takes place (Aitken et al 2014, Fernandez-Diez et al 2015, the zygote being responsible for repairing the sperm damage.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 It is possible that some ICSI patients with low implantation or pregnancy may result from injection of inadequate or poor-quality sperm, for example, with abnormal morphological or DNA damaged sperm. [6][7][8][9] As the majority of ICSI patients are male factor infertility and they have variable abnormal ejaculated sperm, particularly those with high proportion of DNA damaged sperm, subjective manual method is inconsistent or unable to select a most competent sperm for ICSI. Thus it is necessary to develop an objective and efficient method for selection of the most competent sperm for ICSI.…”
mentioning
confidence: 99%